Child functioning and disability in children living with human immunodeficiency virus in a semi-rural healthcare setting in South Africa - Stacy T. Maddocks; Lindokhule Mthethwa; Verusia Chetty (AOSIS, 2020)
Background: Children living with HIV (CLHIV) often experience HIV-related impairment and disability. Aim: The study sought to understand the level of child functioning and access to rehabilitative care in the context of South African healthcare in order to inform an integrated rehabilitative framework. Setting: District level semi-rural healthcare facility in KwaZulu-Natal. Methods: The Washington Group/United Nations International Children's Emergency Fund Module on Child Functioning, was administered to carers of CLHIV aged between 5 and 10 years, and accessing care at the study setting. Results: Forty-four caregivers of children receiving treatment from June 2018 to March 2019, at the facility, participated. Four (9.1%) children had difficulty with seeing, 13 (29.5%) children had difficulty with hearing and 10 (22.7%) children had difficulty with walking. In the cognitive and behavioural domains, 17 (38.6%) children reported difficulties in communication and concentration, with 16 (36.4%) children experiencing difficulties in learning and remembering. Difficulties reported in accepting change and controlling behaviour were both experienced by 23 (52.3%) children. Although many children experiencing impairments were referred for rehabilitation, many caregivers did not follow-up after the initial assessment, because of financial constraints, lack of time and transport restrictions. Conclusion: Functional difficulties were frequently experienced by children living with HIV. Disability screening would be beneficial at various points of care to promote early identification and timely referral to healthcare professionals. Decentralising rehabilitative care to homes and communities could offer a solution to some of the reported barriers to accessing care.